Pengaruh Gaya Kepimpinan Direktur terhadap Kinerja Dosen dan Karyawan ASMTB Periode 2015-2016 - Sofiatiningsih Sofiatiningsih (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
Lecturers and employees of ASMTB at this time show less optimal performance. The lack of optimum utilization of existing human resources, lack of motivation lecturers and employees to show their best performance, work climate created in conditions of less creativity, visible lack of supervision. The problem is allegedly influenced by the leadership style of the ASMTB director. To the authors want to reveal the influence of Leadership Style Effects on Lecturer and Employee Performance ASMTB Period 2015-2016. The method used in this research is analytical descriptive, which is solving the problem in actual way by collecting data, compiling, classifying it further analyze and interpret. The population in this study is all lecturers and employees of ASMTB 2016, totaling 29 people, consisting of 24 lecturers and 5 employees. The design of the research conducted through the survey method that comes from primary data, in the form of answers to the list of questions asked to lecturers and employees with Likert scale. The results showed that the leadership style ASMTB director 2015-2016 period is a motivational style with a total scor of 128. This leadership style significant effect on the performance of lecturers and employees ASMTB can be seen at the correlation value of 0.673, then the value of determination coefficient. The director's style in leading this institution is poorly utilized so that the performance of lecturers and employees is not optimal, according to the calculation result through the coefficient of determination by using SPSS for windows software shows the result of 45.29% leadership style 2015-2016 period influence on the performance of lecturers ASMTB, the rest of 54.71% influenced by other factors not examined by the author, is a study material for further research. Keywords: Employee Performance, Leadership Style, Lecturer.